2010
DOI: 10.1086/655465
|View full text |Cite|
|
Sign up to set email alerts
|

Influenza Vaccination and Intention to Receive the Pandemic H1N1 Influenza Vaccine among Healthcare Workers of British Columbia, Canada: A Cross-Sectional Study

Abstract: Vaccination campaigns for pandemic H1N1 vaccine should use messages that emphasize the risk of illness among younger people and the opportunity to protect loved ones by getting the vaccine and should address concerns about the safety and effectiveness of the vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
52
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 19 publications
(10 reference statements)
10
52
2
1
Order By: Relevance
“…Among the HCPs we surveyed, the willingness to be vaccinated against pH1N1was high. Similar acceptance rates for vaccination have been reported in other studies among the general population (Mexico 80% [28], Canada 69% [29] and 75% [30], and 89% in Kenya [31]). However, our results are markedly different from those in other studies that have reported a low willingness to be vaccinated in HCPs [13][14][15][32][33][34][35].…”
Section: Discussionsupporting
confidence: 88%
“…Among the HCPs we surveyed, the willingness to be vaccinated against pH1N1was high. Similar acceptance rates for vaccination have been reported in other studies among the general population (Mexico 80% [28], Canada 69% [29] and 75% [30], and 89% in Kenya [31]). However, our results are markedly different from those in other studies that have reported a low willingness to be vaccinated in HCPs [13][14][15][32][33][34][35].…”
Section: Discussionsupporting
confidence: 88%
“…In the studies performed, the most important reasons for accepting vaccination with 2009 pandemic influenza vaccine were protecting himself/herself and the patients from the disease, fear of transmitting the disease to the people close to them and following the recommendations of the health authorities [21,22]. However in our study, most frequent reasons to accept vaccination were being in the high risk group and the presence of a pandemic.…”
Section: Discussioncontrasting
confidence: 48%
“…This was manifested by a spectrum of attitudes, such as: perceiving susceptibility to swine flu as low, believing that the epidemic was not serious, believing the swine flu was a mild disease. 74,[83][84][85]89,92,93,95,96,98,100 These motives became very apparent in studies conducted at later time points, but was observed also in earlier surveys as well.…”
Section: Acceptance Of the A/h1n1 Vaccine: When Anticipation And Realmentioning
confidence: 71%
“…74,83,86,[92][93][94]96,99 Interestingly, lay individuals did not relate directly to the fact that the H1N1v was a novel vaccine and that it was subject to accelerated evaluation legislation processes. (7) The perception of the threat as not being serious was a very dominant motive in many of the studies on H1N1v acceptance.…”
Section: Acceptance Of the A/h1n1 Vaccine: When Anticipation And Realmentioning
confidence: 99%